1967
DOI: 10.1104/pp.42.8.1077
|View full text |Cite
|
Sign up to set email alerts
|

An Effect of Light on the Production of Ethylene and the Growth of the Plumular Portion of Etiolated Pea Seedlings

Abstract: Summiarv. The produiction of ethylene by etiolated pea epicotyls (Pisuim sativum11 L., cv. Alaska) is confined to the plumule and plumular hook portion of the epicotyl, and occurs at a rate of about 6 pLlkg-l.hr-1. Such a rate is sufficient to give physiologically active concentrations of ethylene within the tissue. Exposure of etiolated seedlings to a single dose of red light caused a transient decrease in ethylenc produiction and a corresponding increase in plumuilar expansion. Far-red irradiation following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
91
1
4

Year Published

1970
1970
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(105 citation statements)
references
References 5 publications
8
91
1
4
Order By: Relevance
“…Our data on ethylene production by parts of the bean hypocotyl hook (Table II) are in agreement with the proposed regulatory role of ethylene in that tissue (15) and the pea epicotyl (12,13).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our data on ethylene production by parts of the bean hypocotyl hook (Table II) are in agreement with the proposed regulatory role of ethylene in that tissue (15) and the pea epicotyl (12,13).…”
Section: Discussionsupporting
confidence: 78%
“…hr, and it opens in red light when the ethylene production drops to 1.3 4l,/kg hr (15). Goeschl et al (12,13) reported a similar response of pea epicotyl ethylene production and growth to red light. Hooks treated with coumarin produced ethylene at 23 to 28 Al/kg hr in some of our tests following 18-hr exposure to the inhibitor (Table II).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In addition, curvature of dgt seedlings gravistimulated in darkness for 20 h was not significantly different from that of dgt plants gravistimulated in red light (data not shown). Whereas red light was previously reported to cause a marked deceleration of ethylene production in pea (Goeschl et al, 1967) and soybean (Samimy, 1978), we observed no effect of either red light or gravistimulation alone on ethylene production in dgt or any other tomato genotype tested. The dgt lesion does, however, render ethylene synthesis sensitive to the simultaneous application of gravity stimulus and red light (Fig.…”
Section: Discussioncontrasting
confidence: 49%
“…The shape of plumular hook as automorphosis seems to be due to the inhibition of hook formation, since during the incubation the angle of plumular hook first increased, and then decreased under 1 G conditions while the decrease in hook angle was suppressed on a 3-D clinostat. Apical hook formation is considered to be modulated by ethylene (Goeschl et al, 1967;Kang et al, 1967). A negative correlation between ethylene production and hook formation using an ethylene biosynthesis inhibitor, and a suppression of ethylene production on a 3-D clinostat have found in etiolated Alaska pea seedlings (Miyamoto et al, 2005b).…”
Section: Inhibition Of Hook Formationmentioning
confidence: 99%